Socio-geographical disparities of obesity and excess weight in adults in Spain: insights from the ENE-COVID study - Gutiérrez-González, Enrique; García-Solano, Marta; Pastor-Barriuso, Roberto; Fernández de Larrea-Baz, Nerea; Rollán-Gordo, Almudena; Peñalver-Argüeso, Belén; Peña-Rey, Isabel; Pollán, Marina; Pérez-Gómez, Beatriz; , the ENE-COVID Study Group (Frontiers in Public Health, 2023)
Background: In Spain, differences in the prevalence of obesity and excess weight according to sex and sociodemographic factors have been described at the national level, although current data do not allow to deepen delve into geographical differences for these indicatorsconditions. The aim was to estimate national and regional prevalences of adult obesity and excess weight in Spain by sex and sociodemographic characteristics, and to explore difference sources of inequalities in its distribution, as well as its geographical pattern. Method: ENE-COVID study was a nationwide representative seroepidemiological survey with 57 131 participants. Residents in 35 893 households were selected from municipal rolls using a two-stage random sampling stratified by province and municipality size (April-June 2020). Participants (77.0% of contacted individuals) answered a questionnaire which collected self-reported weight and height, as well as different socioeconomic variables, that allowed estimating crude and standardized prevalences of adult obesity and excess weight. Results: Crude prevalences of obesity and excess weight were higher in men (obesity: 19.3% vs. 18.0 %; excess weight: 63.7% vs. 48.4%), while severe obesity was more prevalent in women (4.5% vs. 5.3%). These prevalences increased with age and disability, and decreased with education, census tract 2 This is a provisional file, not the final typeset article income and municipality size. Differences by educational level, relative census income, nationality or disability were clearly higher among women. Obesity by province ranged 13.3%-27.4% in men and 11.4%-28.1% in women; excess weight ranged 57.2%-76.0% in men and 38.9%-59.5% in women. The highest prevalences were located in the southern half of the country and some north-western provinces. Sociodemographic characteristics only explained a small part of the observed geographical variability (25.2% obesity). Conclusion: Obesity and overweight have a high prevalence in Spain, with notable geographical and sex differences. Socioeconomic inequalities are clearer stronger among women. The observed geographical variability suggests the need to implement regional and local interventions to effectively address this public health problem. The low geographical variability explained by sociodemographic variables suggests that there are other modifiable factors on which to design interventions at national, regional and provincial levels to effectively combat this public health problem.